Nurturing Moral Values Among the Children: Insights from Dance and Drama-Based Learning - ., Ramlan; Rozak, Abdul; ., Fikriyah; ., Nurkholis; Ibrahim, Yusuf (International Journal of Engineering and Technology, 2018)
Emerging the immoral behavior being the challenges in Indonesia during the last few decades needs to have alternative approach implemented in the learning process. The serious reconstruction of the national education curriculum has to be conducted into designing the alternative concept, especially inculcating the moral personality within the exciting programs. Among those programs with offering exciting programs, one of them is dance and drama basis. This paper aims to explore the way to inculcate moral values among the children through dance and drama based learning. Literature analysis was conducted from peer reviewed books and journals using the theme of dance and drama based learning. The results indicate that there are three core basis of delivering learning basis of arts where both refer to sharing the art with a significant professional experience to connect with each other in realizing to feel emotional similarities, potential in shaping moral values. Those are the process of receiving knowledge in the sense of sharpening performance with managing the learning habit. This study is expected to contribute to the conceptual basis on how to inculcate the moral values among the children. Thus, moral education should be optimized within this co-curricular program.Â Â